Ethnographic Analysis of Water Games in Surkhan Oasis - Botir Normuratov (Genius Journals, 2022)
In this article, the types of Uzbek national folk games played in water - “Suvda quvlashmachoq”, “Oq tosh”, “Tez suzish”, “Suv ostida suzish”, “Qaymoq” (“Tosh sakratar”), “Suv ostida turish” etc. the place, by whom to play and the rules of the game were discussed
Keywords: Game; national folk games; children's games; water games